The Role of English in Shaping Linguistic Capital in Bangladesh: A Political Economy Perspective - Hasan Shaikh; Fatematuz Zohora Munmun (Cipta Pustaka Nusantara, 2026)
English in Bangladesh has evolved from colonial roots to come to signify opportunity, privilege, and socio-economic mobility. The role of English in the construction of linguistic capital in Bangladesh is examined in this work from the political economy perspective, theorizing language as commodity, power, and ideology based on a survey of 80 respondents. Findings illustrate almost complete agreement that English proficiency is shaped more by private forces and worldwide pressures than it is by national policy, replicating social stratification. Government efforts are considered by respondents as insufficient to democratize English access, whereas English dominance in elite employment markets still serves to enhance inequality. Yet, these findings also refer to increasing public awareness of English’s structural injustices. Future studies can take longitudinal ethnographic approaches in examining students’ lived experiences in this linguistic economy. Policymakers, in the meantime, need to envision English education as a public good, with a priority for equitable access, multilingual frameworks, and decolonized pedagogy to make English a bridge of inclusive development in Bangladesh.